Macroeconomic and distributive effects of increasing taxes in Spain - Luisa Fuster (SERIEs - Journal of the Spanish Economic Association, 2022)
I assess the macroeconomic and redistributive effects of tax reforms aimed at increasing tax revenue in Spain. To this end, I develop a theory of entrepreneurship that mimics key facts on the wealth and income distribution in Spain. I find two reforms that raise fiscal pressure in Spain to the average value among countries in the Euro area. The first reform involves doubling the average effective tax rate on labor and business income for all individuals whose income is above a threshold level. I find that this reform reduces the inequality in after-tax income, wealth, and consumption. However, it implies a substantial GDP reduction. The second reform increases the flat tax rate on consumption by fifteen percentage points. While this reform does not reduce long-run output, it does not decrease household inequality. All in all, the desirability of the two reforms depends on the government's preferences for reducing inequality at the expense of aggregate output losses.
Keywords: E2; E62; H24; H25; H30; 330; Entrepreneurship; Fiscal pressure; Inequality; Labor supply; Tax revenue; Taxation